Genomic analysis of circulating cell-free DNA infers breast cancer dormancy - Shaw, Jacqueline A.; Page, Karen; Blighe, Kevin; Hava, Natasha; Guttery, David; Ward, Becky; Brown, James; Ruangpratheep, Chetana; Stebbing, Justin; Payne, Rachel; Palmieri, Carlo; Cleator, Suzy; et al.

(untitled) (Genome Research, 2012)
Biomarkers in breast cancer to monitor minimal residual disease have remained elusive. We hypothesized that genomic analysis of circulating free DNA (cfDNA) isolated from plasma may form the basis for a means of detecting and monitoring breast cancer. We profiled 251 genomes using Affymetrix SNP 6.0 arrays to determine copy number variations (CNVs) and loss of heterozygosity (LOH), comparing 138 cfDNA samples with matched primary tumor and normal leukocyte DNA in 65 breast cancer patients and eight healthy female controls. Concordance of SNP genotype calls in paired cfDNA and leukocyte DNA samples distinguished between breast cancer patients and healthy female controls (P < 0.0001) and between preoperative patients and patients on follow-up who had surgery and treatment (P = 0.0016). Principal component analyses of cfDNA SNP/copy number results also separated presurgical breast cancer patients from the healthy controls, suggesting specific CNVs in cfDNA have clinical significance. We identified focal high-level DNA amplification in paired tumor and cfDNA clustered in a number of chromosome arms, some of which harbor genes with oncogenic potential, including USP17L2 (DUB3), BRF1, MTA1, and JAG2. Remarkably, in 50 patients on follow-up, specific CNVs were detected in cfDNA, mirroring the primary tumor, up to 12 yr after diagnosis despite no other evidence of disease. These data demonstrate the potential of SNP/CNV analysis of cfDNA to distinguish between patients with breast cancer and healthy controls during routine follow-up. The genomic profiles of cfDNA infer dormancy/minimal residual disease in the majority of patients on follow-up.